2011
DOI: 10.1017/s0003598x00068459
|View full text |Cite
|
Sign up to set email alerts
|

The Theran eruption and Minoan palatial collapse: new interpretations gained from modelling the maritime network

Abstract: What was the effect on Late Minoan civilisation of the catastrophic destruction of Akrotiri on Thera (Santorini) by volcanic eruption? Not much, according to the evidence for continuing prosperity on Crete. But the authors mobilise their ingenious mathematical model (published in Antiquity 82: 1009–1024), this time to show that the effects of removing a major port of call could have impacted after an interval, as increased costs of transport gradually led to ever fewer routes and eventual economic collapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(37 citation statements)
references
References 12 publications
(12 reference statements)
1
35
0
1
Order By: Relevance
“…This context was chosen so that we can illustrate general methodological principles with a practical archeological example, with the added benefit that it allows us to make direct contact with the classic work of Wilson (1987, 1991). The last decade has seen a rise in the use of such modeling techniques on settlement patterns in a wide range of times and other places: Crete in the second millennium BC (Bevan and Wilson, 2013) or the Middle Bronze Age (Evans et al, 2006;Knappett et al, 2008Knappett et al, , 2011Paliou and Bevan, 2016), Iron Age NE Syria (Davies et al, 2014), early second millennium BC Central Anatolia (Palmisano and Altaweel, 2015), late first Millennium Latenian urbanization (Filet, 2017), early Japan (Mizoguchi, 2009), the Maya lowlands (Ducke and Kroefges, 2008), to give just a few examples. Similar methods can be used when modeling of other types of spatial organization, such as lithic assemblages (Wilson, 2007) to name just one.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This context was chosen so that we can illustrate general methodological principles with a practical archeological example, with the added benefit that it allows us to make direct contact with the classic work of Wilson (1987, 1991). The last decade has seen a rise in the use of such modeling techniques on settlement patterns in a wide range of times and other places: Crete in the second millennium BC (Bevan and Wilson, 2013) or the Middle Bronze Age (Evans et al, 2006;Knappett et al, 2008Knappett et al, , 2011Paliou and Bevan, 2016), Iron Age NE Syria (Davies et al, 2014), early second millennium BC Central Anatolia (Palmisano and Altaweel, 2015), late first Millennium Latenian urbanization (Filet, 2017), early Japan (Mizoguchi, 2009), the Maya lowlands (Ducke and Kroefges, 2008), to give just a few examples. Similar methods can be used when modeling of other types of spatial organization, such as lithic assemblages (Wilson, 2007) to name just one.…”
Section: Resultsmentioning
confidence: 99%
“…This ariadne deterrence function [or ariadne edge potential, labeled AEP in figures, and as used in the studies by Evans et al (2006Evans et al ( , 2012 and Knappett et al (2008Knappett et al ( , 2011] takes the form…”
Section: The Simple Gravity Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…These are shaped by interconnected nodes that usually correspond to habitation nuclei, and extend over territories surpassing the regional scale in such a way that even a change in a single node or link can affect the whole network. Knappett et al (2011) have demonstrated how the disappearance of Akrotiri in the Minoan communication network had important consequences for the whole of the Minoan culture. In the same way, Mol (2014: 193-4) showed how a small island community can be affected and in turn affect itself wider islands' networks in the 14th century North-eastern Caribbean.…”
Section: Methodology: Networking Roman Britainmentioning
confidence: 99%
“…In both cases, the aim is to falsify certain propositions and thus 'restrict the total set of possibilities' (Heinzl et al 2012, p. 32). Finally, Knappet et al have used numerical simulations of network evolution 'to provide a novel perspective on the possible causes for the demise of Cretan Bronze Age palatial society at c. 1500 BC' (Knappett et al 2011(Knappett et al , p. 1008. As they are careful to point out, their simulation does not prove what happened, but it does allow them to propose the hypothesis that increased trading costs after the eruption of Thera lead to greater centralisation of exchange which in turn decreased the resilience of the exchange network, ultimately sowing the seeds of its demise.…”
Section: Expansion (2001 Onwards)mentioning
confidence: 99%